Fluid dynamics and segregation of sand-malt waste mixture in conical spouted bed - Pazin Almeida, Natalia; Lira, Taisa; Silverio, Beatriz Cristina; Vieira Neto, José Luiz; Santos, Kassia (Latin American Journal of Energy Research, 2024)
One of the most traditional sectors of Brazilian agribusiness is the brewing industry. The most used cereal in this process is barley, generating as the main by-product malt waste, a biomass called lignocellulosic. The pyrolysis in spouted bed is a promising technology for renewable energy generation through agro-industrial wastes. Thus, aiming at contributing to the application of the spouted bed as a pyrolysis reactor, the fluid dynamic analyzes of the mixture of malt waste and, sand was carried out. It was observed how the static bed height and biomass mass fraction influence the condition of minimum and critical spout and the segregation of the particles. The correlations analyzed presented good results to predict the minimum spout velocity, with a relative error of 4.83%. For the maximum pressure drop, the best correlation showed relative error of 13.91% and, for pressure drop of minimum spout, a relative error of 5.45%. It was also observed that the base of the bed showed higher segregation rates, with a higher presence of sand particles. Keywords: spouted bed particle segregation, brewer’s spent grain, malt waste, particle mixing, particle segregation.